2021
DOI: 10.1055/a-1396-3718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality benchmarks in adenoma detection in Mexico

Abstract: Background and study aims Several Latin American countries, including Mexico, have reported an increase in colorectal cancer (CRC) mortality. The effectiveness of a colonoscopy in preventing CRC depends on the quality of the procedure, for which the adenoma detection rate (ADR) is one of the most trusted indicators. Awareness of ADR can improve the quality of colonoscopies through proper feedback and training of the specialists. The goal of this study was to estimate the ADR among Mexican endoscopists with exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The ADR for the group that involves fellows was 31.5% (95% CI: 26.7-36.2%), while the attendings alone had 30.4% (95% CI: 26.9-33.9%), with no statistical difference in both groups (p = 0.76). In a recent study by Aguilar et al, they found an ADR of 24.6%, made by Mexican endoscopists, but there were no fellows involved; this is really close to our data from gastroenterology fellows (23%) 16 .…”
Section: Discussionsupporting
confidence: 91%
“…The ADR for the group that involves fellows was 31.5% (95% CI: 26.7-36.2%), while the attendings alone had 30.4% (95% CI: 26.9-33.9%), with no statistical difference in both groups (p = 0.76). In a recent study by Aguilar et al, they found an ADR of 24.6%, made by Mexican endoscopists, but there were no fellows involved; this is really close to our data from gastroenterology fellows (23%) 16 .…”
Section: Discussionsupporting
confidence: 91%